2006
DOI: 10.2353/ajpath.2006.051302
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Collagen Production in Chronologically Aged Skin

Abstract: Reduced synthesis of collagen types I and III is characteristic of chronologically aged skin. The present report provides evidence that both cellular fibroblast aging and defective mechanical stimulation in the aged tissue contribute to reduced collagen synthesis. The reduction in collagen synthesis due to fibroblast aging was demonstrated by a lower in vitro production of type I procollagen by dermal fibroblasts isolated from skin of young (18 to 29 years) versus old (80+ years) individuals (82 +/- 16 versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
322
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 688 publications
(336 citation statements)
references
References 38 publications
10
322
0
4
Order By: Relevance
“…In aged skin, fibroblasts adjacent to fragmented collagen are less stretched, and by inference have lower mechanical tension. 6,85 Our results in collagen lattices demonstrate that collagen fragmentation causes loss of stretch, which results in increased levels of oxidants. Mechanism(s) by which loss of stretch (or mechanical tension) results in increased oxidative stress in fibroblasts is currently unknown.…”
Section: Discussionmentioning
confidence: 85%
“…In aged skin, fibroblasts adjacent to fragmented collagen are less stretched, and by inference have lower mechanical tension. 6,85 Our results in collagen lattices demonstrate that collagen fragmentation causes loss of stretch, which results in increased levels of oxidants. Mechanism(s) by which loss of stretch (or mechanical tension) results in increased oxidative stress in fibroblasts is currently unknown.…”
Section: Discussionmentioning
confidence: 85%
“…We previously reported that fibroblasts in aged human skin display a contracted, rounded morphology with 50% less surface area (Varani et al ., 2006). Therefore, we determined whether reduced fibroblast size in aged skin is associated with reduced TβRII gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…Fibroblasts are unable to attach to the fragmented ECM and therefore cannot exert traction forces needed to spread, and appear contracted. We and others have previously reported that many TGF‐β‐regulated genes involved in ECM production are reduced in aged human skin (Varani et al ., 2006; Quan et al ., 2010). Importantly, TβRII expression is also reduced in aged skin (Quan et al ., 2006; Quan & Fisher, 2015), suggesting that impaired TGF‐β signaling may be a key mediator of reduced ECM production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that mesenchymal stem cells could significantly increase wound healing by activating matrix metalloproteinase 9 and vascular endothelial growth factor. The literature suggests the use of these cells in various therapeutic interventions, such as treatment of ulcers due to surgery or burns, chronic ulcers, treatment resistance in diabetic ulcers, and shallow or deep wrinkles of the skin (18,19).…”
Section: Function Of Fibroblastsmentioning
confidence: 99%